Analysis Smart Class Method Fuzzy Logic Using Arduino Uno - Aprama N; Endra R Y (International Conference on Engineering and Technology Development (ICETD), 2017)
Internet of Things is a technology that allows us to connect the machinery, equipment, and other physical objects with a network of sensors and actuators to obtain data and manage their own performance, thus allowing the machine to collaborate and even act on new information obtained independently(McKineyGlobalInstitute).National electrical energy needs continue to increase. This increase was caused by the use of electrical energy in buildings, industry and factories. On the other hand, electrical energy consumption is also very wasteful society. This is due to lack of attention to the size of power(watts)of electrical equipment used. Smart class room or smart rooms which objects in the room to be controlled easily and efficiently by users, in this case these objects are object selectronics commonly found in a room such as lights, fans, air conditioners, door , whiteboard, etc.Using control system in this project is to use arduino uno so that its use will allow users to control the electronic goods. Based on the above, then this study will analyze the automation of air conditioner by applying fuzzylogic.